1995
DOI: 10.1111/j.1476-5381.1995.tb15100.x
|View full text |Cite
|
Sign up to set email alerts
|

Lack of effect of TNF antibodies on the cardiovascular sequelae of lipopolysaccharide infusion in conscious rats

Abstract: 1 The aims of the present study were to determine the profile of tumour necrosis factor (TNF) release, and the effect of monoclonal antibodies to TNF, on the changes in regional haemodynamics and the responses to vasodilator and vasoconstrictor challenges, during a continuous 24 h low dose infusion of lipopolysaccharide (LPS) in conscious rats. 2 Male Long Evans rats were chronically instrumented for measurement of regional haemodynamics (renal, superior mesenteric and hindquarters) and were challenged with 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
15
2

Year Published

1998
1998
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 37 publications
(77 reference statements)
4
15
2
Order By: Relevance
“…In the light of this observation it could be suggested that bolus injection of LPS activates cytokine cascades in a way not seen with LPS infusion. However, we have shown that LPS infusion (as here) causes substantial elevation of plasma TNF‐α levels (Waller et al , 1995). So, another interpretation is that only those effects of LPS infusion that were changed by antibody pretreatment (i.e., the initial hindquarters vasodilatation and the recovery from the initial fall in MAP) involved TNF‐α and/or IL‐1β.…”
Section: Discussionmentioning
confidence: 66%
“…In the light of this observation it could be suggested that bolus injection of LPS activates cytokine cascades in a way not seen with LPS infusion. However, we have shown that LPS infusion (as here) causes substantial elevation of plasma TNF‐α levels (Waller et al , 1995). So, another interpretation is that only those effects of LPS infusion that were changed by antibody pretreatment (i.e., the initial hindquarters vasodilatation and the recovery from the initial fall in MAP) involved TNF‐α and/or IL‐1β.…”
Section: Discussionmentioning
confidence: 66%
“…The aim of this study was to measure the effects of lipopolysaccharide (LPS)‐induced endotoxaemia on the expression of Akt, FOXO and its downstream targets, to examine the potential dual role of FOXO in both muscle protein loss and impairment of carbohydrate oxidation in vivo during sepsis. To investigate this, conscious, chronically instrumented rats were infused intravenously with a non‐lethal dose of bacterial LPS, as a clinically relevant model of endotoxaemia that results in a systemic inflammatory response syndrome and represents the early stages of clinical sepsis (Waller et al 1995).…”
mentioning
confidence: 99%
“…Vary et al utilized an intra‐abdominal abscess model of sepsis, which developed over 3–7 days; they provided no information on changes occurring in the first 24 h of the septic challenge (Vary et al 1998). We have previously assessed the haemodynamic changes produced by continuous infusion of lipopolysaccharide (LPS) in conscious rats, and have shown that in this experimental protocol, the hyperdynamic circulatory state mimics that seen in the early stages of clinical sepsis (Waller et al 1995). Therefore, in the present study, we used the LPS infusion model to examine changes in fast‐twitch muscle, which is known to be highly susceptible to sepsis (Tiao et al 1997; Wray et al 2003).…”
mentioning
confidence: 99%